Sunagoke Moss (Racomitrium japonicum) Used for Greening Roofs Is Severely Damaged by Sclerotium delphinii and Protected by a Putative Bacillus amyloliquefaciens Isolate - Tamura, Mako; Tanabe, Minatsu; Valkonen, Jari P. T.; Akita, Motomu (Frontiers in Microbiology, 2019)
Mosses are ecologically important plants also used for greening, gardening, and decorative purposes. Knowledge of the microbial flora associated with mosses is expected to be important for control and preservation of global and local environments. However, the moss-associated microbial flora is often poorly known. Moss-associated fungi and bacteria may promote plant growth and pest control, but they may be alternative hosts for pathogens of vascular plants. In this study, the fungus Sclerotinia delphinii was identified for the first time as a pathogen that causes severe damage to Sunagoke moss (Racomitrium japonicum). This moss is used for greening roofs and walls of buildings in urban environments owing to its notable tolerance of environmental stresses. Inoculation with the S. delphinii strain SR1 of the mono- and dicotyledonous seed plants Hordeum vulgare, Brassica rapa var. pekinensis, Lactuca sativa, and Spinacia oleracea, in addition to the liverwort Marchantia polymorpha and the moss Physcomitrella patens, showed that the fungus has a wide host range. Infection with SR1 progressed more rapidly in non-vascular than in vascular plant species. Studies with P. patens under controlled conditions showed that SR1 secreted a fluid during infection. Treatment with the secretion induced production of reactive oxygen species in the moss. Endogenous peroxidase partially inhibited SR1 infection of P. patens. A bacterial isolate, most likely Bacillus amyloliquefaciens, that coexists with R. japonicum was antagonistic to SR1 growth. Taken together, the present results suggest that fungal infection of mosses may be prevented by a peroxidase secreted by the moss and an antagonistic bacterium coexisting in the moss habitat. The findings suggest that there is potential to apply biological control measures for protection of mosses against fungal pathogens.